ANALYSIS OF LEVEL OF SATISFACTION OF POSTGRADUATE TRAINEES ON SURGICAL FLOOR - Hameed, Tahira; Zia, Naeem; Khan, Haleema Saadia; Zia, Ammarah; Ahmed, Rameez; Hameed, Aurangzaib; Ahmed, Murtaza; khan, Abdul Qadeer (Journal of Ayub Medical College Abbottabad, 2019)
Background Organizations flourish with a satisfied workforce. There is little known information on demographic characteristics and motivators for job satisfaction among Pakistani postgraduate trainees in surgery. Job satisfaction is predicted by intrinsic motivators (personal growth and perceived ability to work) and extrinsic motivators (perceived social support). Work family interference/enhancement and job stressors (workload and long working hours) also impacts job satisfaction; predicting overall life satisfaction. This study aims at examining life satisfaction predicted by personal and professional characteristics. Method The postgraduate trainees in the public and private hospitals of Rawalpindi and Islamabad were surveyed using validated measures of life satisfaction, personal growth, perceived social support, perceived ability to work, work family interference/enhancement, job stressors, co-workers support, supervisors support, and job satisfaction from September 15 to December 28, 2017. Results Personal growth, perceived ability to work, availability of social support, and work family enhancement positively correlate to job and life satisfaction. Work life interference and job stressors negatively relate to job and life satisfaction. Job satisfaction is also partially mediated by intrinsic and extrinsic motivators on life satisfaction, whereas job stressors weakened the relationship between job satisfaction and life satisfaction. Long working hours is negatively related to job satisfaction and life satisfaction. Conclusion Life satisfaction is predicted by job satisfaction that is characterized intrinsic and extrinsic motivators. Healthcare organizations face challenge of providing reduced working hours, increased salaries, supportive working environment, and increased supervision to enhance the job satisfaction of employees and to improve the functioning of the healthcare environment. Keywords: Life satisfaction; job satisfaction; postgraduate trainees; long working hours